Evaluating Middle School Students’ Spatial-Scientific Performance within Earth/Space Astronomy in Terms of Gender and Race/Ethnicity - Jennifer Wilhelm; Michael Toland; Merryn Cole (Journal of Education in Science, Environment and Health)
Differences were examined between groups of sixth grade students’ spatial-scientific development pre/post implementation of an Earth/Space unit. Treatment teachers employed a spatially-integrated Earth/Space curriculum, while control teachers implemented their Business as Usual (BAU) Earth/Space units. A multi-level modeling approach was used in a hierarchical manner to evaluate student performance on the Purdue Spatial Visualization: Rotation test (PSVT-Rot) and on the Lunar Phases Concept Inventory (which included four spatial domains), while controlling for two variables (gender and race/ethnicity) at the student level and one variable (teaching experience) at the teacher level. Results showed Treatment girls achieved higher LPCI Periodic Patterns (PP) spatial domain post-scores than girls in the BAU group. A gender gap was also observed (in favor of boys) within the BAU group for PP domain post-scores, while no gap was shown within the Treatment group. In addition, results for PP suggest Students of Color tended to have lower PP scores than White students (Effect Size = .29), and that higher pretest PP scores tended to lead to higher posttest PP scores, after adjusting for other student and teacher characteristics. The only statistically significant predictor of the PSVT-Rot posttest scores were scores on the respective pretest.